Development of Cattle Embryo Through In Vitro Technique Using Epidermal Growth Factor as A Media Supplement - Prasad, Shiba; C., Prakash; K., Rohit; Karunakaran, M.; Santra, A.; Das, Subrata K. (International Journal of Bio-resource and Stress Management, 2018)
The present study was conducted to produce cattle embryos through in vitro culture by supplementing media with epidermal growth factor. Immature cattle oocytes were collected from slaughterhouse ovaries, washed 5-6 times and cultured in maturation media (TCM-199+10% FBS+5 µg ml-1 FSH-P+0.33 mM sodium pyruvate+50 µM β-Mercaptoethanol+50 µg ml-1 gentamicin sulfate) supplemented with epidermal growth factor with three different concentrations (5, 10 and 20 ng ml-1) for 24 h. in 5% CO2 incubator at 38.5 °C with maximum humidity. After 24 h matured oocytes were allowed for fertilization with capacitated sperms in Fert-BO media at 38.5 °C in CO2 incubator. After 15-18 h of sperm-oocyte co-incubation, the cumulus cells were washed off from the oocytes by gentle pipetting in washing medium. The oocytes were then washed 1-2 times with modified Charles Rosenkrans 2 amino acid (mCR2aa) media and cultured in 100 µl droplet supplemented with epidermal growth factor, and cultured for cleavage. After 48 h cleavage was checked and further co-cultured with oviductal cells for development. In the present study the cleavage rate and morula formation rate were significantly higher in the treatment group as compared to control group. The mean percentage of cleavage rate was 41.63±1.92 in control group. The highest mean percentage of cleavage rate was 55.13±1.45 in 10 ng ml-1 treatment groups. From the present study it could be concluded that epidermal growth factor may have induced the cleavage after fertilization.